2021
DOI: 10.1126/sciadv.abe3588
|View full text |Cite
|
Sign up to set email alerts
|

A tumor microenvironment–induced absorption red-shifted polymer nanoparticle for simultaneously activated photoacoustic imaging and photothermal therapy

Abstract: Tumor microenvironment–responsive therapy has enormous application potential in the diagnosis and treatment of cancer. The glutathione (GSH) level has been shown to be significantly increased in tumor tissues. Thus, GSH can be used as an effective endogenous molecule for diagnosis and tumor microenvironment–activated therapy. In this study, we prepared a tumor microenvironment–induced, absorption spectrum red-shifted, iron-copper co-doped polyaniline nanoparticle (Fe-Cu@PANI). The Cu(II) in this nanoparticle c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
85
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(97 citation statements)
references
References 45 publications
1
85
0
Order By: Relevance
“…[22] For example, TME-related overexpressed GSH can simultaneously activate the PAI and photothermal therapy (PTT) functions of specifically designed nanoparticles. [23] TME-activated nanoprobes also present the advantages of accuracy, high efficiency, low interference of background signal, and only slight damage to normal tissue. So far, few studies have reported on TME-activated nanoprobes exploiting the NIR-II biological window.…”
Section: Introductionmentioning
confidence: 99%
“…[22] For example, TME-related overexpressed GSH can simultaneously activate the PAI and photothermal therapy (PTT) functions of specifically designed nanoparticles. [23] TME-activated nanoprobes also present the advantages of accuracy, high efficiency, low interference of background signal, and only slight damage to normal tissue. So far, few studies have reported on TME-activated nanoprobes exploiting the NIR-II biological window.…”
Section: Introductionmentioning
confidence: 99%
“…275–277 Therefore, developing GSH probes is of interest in understanding its role in cancer development and to facilitate the application of GSH-targeted cancer therapy. Due to the deep tissue penetration of PA imaging, many activatable PA probes have been developed as tools to study the in vivo behavior of GSH, 278–289 and here we introduce some recent progress in this area.…”
Section: Activatable Pa Probesmentioning
confidence: 99%
“…23c). 290 Utilizing the reductive nature of GSH, the Cu 2+ in the Fe-Cu@PANI probe can undergo a redox reaction to yield NPs with a size reduction and a red-shift of the absorbance maximum. To evaluate the PA imaging performance of Fe-Cu@PANI, the probe was injected into both the normal muscle tissue (bearing no tumor) and the xenograft 4T1 tumor side of the mice.…”
Section: Activatable Pa Probesmentioning
confidence: 99%
“…As a result, the penetration depth and imaging resolution were greatly enhanced compared with optical imaging techniques. [106][107][108] In this process, PA agents, including organic dyes, [109][110][111] metallic nanoparticles, [112][113][114] carbon nanotubes, [115,116] and 2D materials, [117][118][119] have been widely explored in the past decade. However, most of them suffered severely because of their intrinsic imperfections in poor photostability and low biocompatibility.…”
Section: Photoacoustic Imagingmentioning
confidence: 99%